Effect of opening depth of oblique weir with an opening on river bed morphology. Issue 1 (October 2021) - Une, H; Ohmoto, T; Kuranaga, K
Abstract: In this study, we focused on the fact that an oblique weir with an opening activates the fluidity of the sediment compared with a conventional continuous fixed one and examined the removal function of the sediment deposited upstream of the weir. Experimental results showed that the weir with the opening increased the fluidity of the sediment deposited upstream of the weir and lowered the riverbed. The scouring section upstream of the weir was divided into a gradually varied flow section and a local flow section based on the bed topography. In the gradual flow section, the descent of water level and riverbed increases linearly as the opening depth increases. In addition, it was shown that the local scour shapes upstream and downstream of the weir were similar to each other as a result of normalization on the representative scale of vertical and transverse shapes. By creating the opening of the oblique weir, the magnitude of the downward flow generated near the left bank was reduced from 45% to 34% of the non-open weir.